Market Day: Strategi Menumbuhkan Jiwa Kewirausahaan pada Anak di Dusun Cempaka Putih Desa Punggur Kecil - Vannes Lamhot; Rangga Wahyu Pratama; Dimas Dimas; Yudha Rizki Dwi Prakoso; Jhosua Praypsworsh (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Community service was carried out in Cempaka Putih Hamlet, Punggur Kecil Village, Kubu Raya Regency with the aim of developing an entrepreneurial spirit in children. The main problem raised was the children's lack of knowledge about entrepreneurship, both in terms of concept and practice. Entrepreneurship is not only related to economic aspects, but also trains the ability to innovate, critical thinking, cooperation, and problem-solving skills. The market day program was created to help children understand the concept of entrepreneurship, implemented with an Asset-Based Community Development (ABCD) approach that focuses on individual and community development. This program consists of delivering material on the basics of entrepreneurship and direct practice through selling activities. The results of the activity showed that market day had a positive impact on the development of children's creativity, ability to work together, development of skills, critical thinking skills, problem solving, innovation and entrepreneurial spirit. Children were more enthusiastic, creative and able to cooperate in practicing simple entrepreneurial concepts. This activity not only introduced the concept of entrepreneurship but also became a means to foster an entrepreneurial spirit from an early age.